Political Asylum Deceptions The Culture of Suspicion - Bohmer, Carol (Springer International Publishing, 2018)
Millions of refugees desperately need humanitarian protection, yet today asylum seekers are increasingly labeled liars, criminals, and even terrorists. How did we get to the point where society's most vulnerable are enveloped by a cloud of hostile suspicion? In this rigorous and highly readable book Bohmer and Shuman resume their highly productive collaboration to highlight the relentless governmental focus on pseudo-science, evidence, truth, credibility, and proof, and examine real malfeasance stories. Illicit activities and complex webs of transnational mobility ultimately contribute to claims of fraud, corruption, and deceit, trapping countless numbers and further eroding compassion and understanding.' -Benjamin N. Lawrance, Editor-in-Chief, African Studies Review 'In grappling with the issue of 'deception' in the asylum process, Bohmer and Shuman tackle some of the most important and difficult questions facing both advocates and decision makers. What counts as evidence? Is it enough to 'tell your story'? When is it okay to lie? And do the deceptions that are an inevitable consequence of the complex and messy situations from which people flee invalidate their claims for protection? Sharply observed and carefully written, this is a 'must read' for anyone who believes that 'truth' is almost always more complex than it seems.' - Heaven Crawley, Chair in International Migration at the Centre for Trust, Peace and Social Relations, Coventry University, UK 'From stories through 'facts', evidence and 'having a case', to being a subject in a world of restrictions and deception: this is the journey described in this book, and it is the journey of large numbers of asylum seekers in the 21st century. Richly documented and carefully argued, Bohmer and Shuman's book must be placed among the handful of studies that take our understanding of the contemporary asylum system genuinely forward.' -Jan Blommaert, Professor and Director of Babylon, Center for the Study of Multicultural Societies, Tilburg University, Netherlands.